2019
DOI: 10.1111/nbu.12362
|View full text |Cite
|
Sign up to set email alerts
|

The BiZiFED project: Biofortified zinc flour to eliminate deficiency in Pakistan

Abstract: Zinc deficiency is a global public health problem, affecting ~17% of the world's population, with the greatest burden in low‐ and middle‐income countries. An increasing body of evidence suggests that biofortification may be a cost‐effective and sustainable approach to reducing zinc and other micronutrient deficiencies. Biofortification enhances the nutritional quality of food crops through conventional plant breeding techniques and agronomic practices. This paper presents ongoing research on biofortification i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…There were, however, significant reductions in self‐reported morbidity (including pneumonia and vomiting) in the high zinc wheat flour group compared with the group consuming low zinc wheat flour. The BiZiFED project is currently underway in Pakistan to further investigate the effect of zinc‐biofortified wheat on zinc status using a variety of biomarkers (Ohly et al 2019). While zinc‐biofortified wheat lines have been successfully developed by identifying and exploiting natural genetic variation and through the use of fertilisers, both techniques have proven to be less effective for significantly increasing iron in wheat.…”
Section: Future Trendsmentioning
confidence: 99%
“…There were, however, significant reductions in self‐reported morbidity (including pneumonia and vomiting) in the high zinc wheat flour group compared with the group consuming low zinc wheat flour. The BiZiFED project is currently underway in Pakistan to further investigate the effect of zinc‐biofortified wheat on zinc status using a variety of biomarkers (Ohly et al 2019). While zinc‐biofortified wheat lines have been successfully developed by identifying and exploiting natural genetic variation and through the use of fertilisers, both techniques have proven to be less effective for significantly increasing iron in wheat.…”
Section: Future Trendsmentioning
confidence: 99%
“…Pakistani soils are Zn-deficit, which not only leads to low Zn contents in edible parts of the crops, but also affects their growth and productivity [ 9 , 10 ]. Zinc fertilization not only improves grain Zn concentration, but also important for the growth and productivity of mungbean [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The programme is working (i) to evaluate the role of Zincol-2016 in improving the Zn and Fe status in children and girls living in low resource communities (ii) spatial modeling using soil and crop data to predict the grain Zn concentration variations due to soil properties and farm management practices, and (iii) to study the socio economic and market constraints in uptake of biofortified wheat cultivars. The BiZiFED project survey reported that more than half of the females were Zn deficient from the randomized controlled trial (Ohly et al, 2019). In Pakistan, the research on agronomic biofortification interventions to enhanced grain Zn deposition and bioavailability in cereals (wheat and rice) has been done by many scientists (Hussain et al, 2012a,b;Farooq et al, 2018;Rehman et al, 2018b,c,d;Rashid et al, 2019;Nadeem et al, 2020a,b).…”
Section: Status Of Zinc Biofortificationmentioning
confidence: 99%